Substantial in-vitro and emerging clinical evidence supporting immediate dentin sealing - Haitham Elbishari; Emad S. Elsubeihi; Taif Alkhoujah; Heba E. Elsubeihi (Elsevier, 2021)
The application of resin adhesive to freshly cut dentin after teeth preparation, the so-called immediate dentin sealing (IDS) has been suggested as an alternative to the delayed dentin sealing (DDS), a technique in which resin adhesive is applied just before final bonding of indirect restorations.The aim of this review is to demonstrate the evidence of the claimed advantages made by the proponents of IDS technique.The results of this review revealed substantial in-vitro evidence supporting the IDS benefits including improved bond strength, reduced dentin permeability, improved restorations' adaptation, and increased fracture strength of the restorations. Clinical studies have shown that IDS improves survival of ceramic laminate veneers bonded to prepared teeth with increased exposure of dentin. Moreover, it has been shown that IDS reduces post-cementation hypersensitivity in full coverage restorations, which is characterized by exposure of a large number of dentinal tubules. The selection of filled resin adhesive that is capable of producing thick adhesive layer appears to contribute to the success of the technique. Furthermore, careful management of the oxygen inhibition layer before conventional impression making and proper cleaning of the residual temporary cement used with provisional restorations appears to affect the outcome of the restorations.